Study of Etiology of Vitreous Hemorrhage in Adult Patients Attending Tertiary Care Eye Center in Western India - Neha Desai; Margi Panchal; Somesh Aggarwal; Puja Negi (Delhi Journal of Ophthalmology)
Aim: The aim is to study the etiology of vitreous hemorrhage in adult patients attending tertiary care eye center and to find the most common systemic association of vitreous hemorrhage in our hospital scenario. Materials and Methods: This was an observational, cross-sectional study done over a period of 2 years at a tertiary referral center in Western India. Around 70 adult patients with vitreous hemorrhage were evaluated to find the etiology. Detailed history was taken, followed by complete ocular examination which included best-corrected visual acuity, fundus examination, and ultrasound B scan, when the media was hazy to assess vitreous and retina. Systemic investigations were done where needed. Results: In our study, 67% were male and 33% were female. Bilateral involvement was found in 19%. Maximum (36%) patients were between the age of 21–35 years. Proliferative diabetic retinopathy (PDR) (34%) was the most common cause of vitreous hemorrhage in our study, followed by trauma (26%) and diabetes mellitus being the most common systemic association of vitreous hemorrhage. Conclusion: Common etiology for vitreous hemorrhage was PDR followed by trauma. Adequate laboratory investigations are also needed to correlate systemic associations of vitreous hemorrhage and to guide for proper treatment.